Management Options to Reduce Phosphorus Leaching from Vegetated Buffer Strips. Issue 2 (1st March 2019) - Hille, Sandra; Graeber, Daniel; Kronvang, Brian; Rubæk, Gitte H.; Onnen, Nils; Molina‐Navarro, Eugenio; Baattrup‐Pedersen, Annette; Heckrath, Goswin J.; Stutter, Marc I.
Abstract : Vegetated buffer strips (VBS) between agricultural areas and surface waters are important retention areas for eroded particulate P through which they may obtain critically high degrees of P saturation imposing high risk of soluble P leaching. We tested topsoil removal and three harvesting frequencies (once, twice, or four times per year) of natural buffer vegetation to reduce P leaching with the aim to offset erosional P accumulation and high degrees of P saturation. We used a simple numerical time‐step model to estimate changes in VBS soil P levels with and without harvest. Harvesting offset erosional deposition as it resulted in an annual ammonium oxalate‐extractable P reduction of 0.3 to 2.8% (25‐cm topsoil content) in soils of the VBS and thus, with time, reduced potential P leaching below a baseline of 50 μg L −1 . Topsoil removal only marginally reduced potential leaching at two sites and not anywhere near this baseline. The harvest frequency only marginally affected the annual P removal, making single annual harvests the most economical. We estimate 50 to 300 yr to reach the P leaching baseline, due to substantial amounts of P accumulated in the soils. Even in high‐erosion‐risk situations in our study, harvesting reduced soil P content and the P leaching risk. We suggest harvesting as a practical and efficient management to combat P leaching from agricultural VBS, not just for short‐term reductions of dissolved P, but also for reductions of the total soil P pool and for possible multiple benefits for VBS. Core Ideas: Annual harvesting offsets erosional P inputs into vegetated buffer strips (VBS). Decades of annual harvesting can effectively reduce P leaching from VBS. Annual harvest frequency only marginally affects P removal. Topsoil removal cannot reduce P leaching from VBS. Without management, P accumulates in VBS to the point of harmful leaching.